Huge thoracic tracheal tumor related to acute respiratory distress syndrome - Massine El Hammoumi; Adil Zegmout; Fouad Nya; Mohamed Bhairis; Marius Kamdem; El Hassane Kabiri (Termedia Publishing House, 2021)
Adenoid cystic carcinoma of the trachea (ACCT) is an unusual low-grade tumor from the tracheal and bronchial wall salivary glands. ACCT occurs most commonly in the upper trachea, being found in the articular cartilage in the posterior part of the trachea.  We report the case of a patient with the rare condition of tracheal ACC who presented in an emergency condition that was successfully treated with a combination of surgery and radiotherapy.